ChemInform Abstract: The Trifluoromethyl Group in Transition Metal Chemistry. Issue 1 (3rd January 2013) - Garcia‐Monforte, M. Angeles; Martinez‐Salvador, Sonia; Menjon, Babil
Abstract Review: ca. 200 refs.